Head-shaking-induced nystagmus reflects dynamic vestibular compensation: A 2-year follow-up study - Striteska, Maja; Valis, Martin; Chrobok, Viktor; Profant, Oliver; Califano, Luigi; Syba, Jaroslav; Trnkova, Katerina; Kremlacek, Jan; Chovanec, Martin (Frontiers in Neurology, 2022)
PURPOSE: We aimed to assess the ability of a head-shaking test to reflect vestibular compensation in patients after unilateral peripheral vestibular loss and provide missing evidence and new insights into HSN features during a two-year follow-up period. BACKGROUND: Head-shaking induced nystagmus (HSN) may follow prolonged sinusoidal head oscillation. In subjects with vestibular function asymmetry, HSN is often observed, usually beating toward the functionally prevalent ear, and can be followed by a reversal of its direction. STUDY DESIGN: A prospective case-control observational study. SETTINGS: Academic, tertiary referral center. METHODS: We followed 38 patients after the acute unilateral vestibular loss (22 vestibular neuronitis patients, 16 patients after vestibular neurectomy) and 28 healthy controls during four consecutive visits over two years. All participants underwent a complex vestibular assessment consisting of spontaneous nystagmus, caloric test, head-shaking test, video head impulse test (vHIT), TUG (time up and go test), and the Dizziness Handicap Inventory (DHI) questionnaire. We established the criteria for the poorly-compensated to assess different compensation behavior and results in these. RESULTS: We found time-related HSN decrease (rho < -0.84, p < 0.001) after unilateral vestibular loss. In the compensated patients, the HSN intensity reached a control group level after two years of follow-up; TUG and DHI also improved to normal; but caloric and vHIT tests remained abnormal during all follow-ups, indicating chronic vestibular deficit. On the contrary, the poorly-compensated patients showed well-detectable HSN during all follow-ups; TUG remained abnormal, and DHI showed at least a moderate deficit. CONCLUSIONS: Our study showed that after a unilateral peripheral vestibular loss, the HSN intensity exponentially decreased in time, reflecting the improvement of dynamic ability and self-perceived deficit. HSN tended to decline to the control group's value once vestibular compensation was satisfactory and sufficient for a patient's everyday life. On the contrary, well detectable HSN in the poorly compensated patients with insufficient clinical recovery confirmed the potential of HSN to reflect and distinguish between sufficient and insufficient dynamic compensation. HSN could serve as an objective indicator of stable unilateral vestibular loss.